Perlindungan Hukum Terhadap Anak Dalam Penerbitan Surat Keterangan Catatan Kepolisian - Wardana, Andi Kusuma; Simangunsong, Frans (Media Hukum Indonesia (MHI), 2026)
atan kriminal anak dalam surat keterangan catatan kepolisian yang tidak ada pembeda antara usia anak dan usia dewasa.. Abstract: Based on Indonesian laws and regulations, this research attempts to ascertain and evaluate the legal protection of children in the issue of Police Record Certificates (SKCK). "Legal Protection of Children in the Issuance of Police Record Certificates" is the title of this thesis. The research employs the statutory approach and the conceptual approach as part of the Normative Legal Research technique. The creation of the problems discussed are: (1) How are the legal regulations for child SKCK according to Indonesian law?, (2) Does the issuance of SKCK provide a guarantee of protection for the confidentiality of data on children's past memories in the issuance of Police Record Certificates? From this approach, it is produced that the first problem formulation will discuss the legal regulations for child protection in the issuance of police record certificates according to Indonesian law. The assurance of protection for the confidentiality of information about children's prior memories in the issue of Police Record Certificates for children pertaining to the rights of children who have been in legal trouble will be covered.